Effect of Various Polyols on the Acid-Denatured States of Champedak Galactose-Binding Lectin - Kameel, Nurul Iman Ahamed; Shuib, Adawiyah Suriza; Tayyab, Saad (Bentham Science Publishers, 2018)
Background: Champedak galactose-binding (CGB) lectin is a tetrameric protein with noncovalently bound monomers, isolated from Artocarpus integer fruit seeds. We had previously reported existence of a structured monomer and an unfolded monomer of CGB lectin at pH 2.5 and pH 1.5, respectively. Polyols are known to induce significant refolding in denatured proteins and stabilize proteins against environmental stresses. Studies on the effect of various polyols on the acid-denatured states of CGB lectin are lacking. Objective: The objective of this study was to investigate the effects of four different polyols, namely, ethylene glycol, erythritol, xylitol and sorbitol on the acid-denatured states of CGB lectin. Methods: CGB lectin was subjected to acid denaturation at pH 2.5 and pH 1.5, both in the absence and presence of 30% (w/v) polyols, i.e. ethylene glycol, erythritol, xylitol and sorbitol. Thermal denaturation of the acid-denatured states was also studied in the absence and presence of these polyols. Different spectroscopic probes such as tryptophan fluorescence, ANS fluorescence and far-UV CD spectral signal were used to monitor structural changes in the acid-denatured states of CGB lectin in the presence of polyols. Results: Presence of erythritol, xylitol and sorbitol in the incubation mixture was found to stabilize the lectin at both pH 2.5 and pH 1.5, as evident from the burial of the hydrophobic clusters and decreased polarity around Trp residues. These polyols also stabilized the acid-denatured states of CGB lectin against thermal denaturation by shifting the thermal transition curves towards higher temperatures. Exposure of the acid-denatured states of CGB lectin, obtained at pH 2.5 and pH 1.5 to 61°C and 51°C, respectively, induced formation of non-native β-structures, compared to that present at 25°C, and this phenomenon was significantly suppressed in the presence of these polyols. Based on the spectral data, both sorbitol and erythritol appeared to exude better stabilizing effect. On the other hand, ethylene glycol was shown to destabilize the aciddenatured states of CGB lectin. Conclusion: Thermal stabilization of the lectin was noticed in the presence of erythritol, xylitol and sorbitol at both pH 2.5 and pH 1.5. These polyols also stabilize the secondary and tertiary structures of the acid-denatured CGB lectin at 25°C. Ethylene glycol was proved to be a destabilizer of the acid-denatured CGB lectin.